Imaging of Common Rheumatic Joint Diseases Affecting the Upper Limbs - Boesen, Mikael; Roemer, Frank; Østergaard, Mikkel; Maas, Mario; Terslev, Lene; Guermazi, Ali (Radiologic Clinics of North America, 2019)
Imaging plays an important role in diagnosis and monitoring of rheumatic diseases of the upper limb. Many rheumatic diseases present with similar clinical pictures, especially in the early stages. Imaging findings in inflammatory and degenerative joint diseases often are nonspecific, especially in the early stages. Imaging findings should be interpreted in light of the clinical context—clinical and paraclinical findings. Good referrals with short clinical history, main clinical findings, disease-involved joint(s), pain distribution, and relevant blood tests increase the likelihood of a correct diagnosis.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Conventional radiography; CT; Imaging; MR imaging; Osteoarthritis; Rheumatoid arthritis; Rheumatology; Ultrasound